ArUcoE: Enhanced ArUco Marker - Kedilioglu, Oguz; Bocco, Tomas Marcelo; Landesberger, Martin; Rizzo, Alessandro; Franke, Jörg (IEEE, 2021)
This paper presents a novel fiducial marker type called ArUcoE. It is obtained from a standard ArUco marker by enhancing it with a chessboard-like pattern. With our approach the pose estimation accuracy of any ArUco marker can easily be increased. Further methods to increase the accuracy are analyzed. By applying a subpixel algorithm to the corner regions we are able to locate the corner points within a pixel and overcome the restriction of pixel-level accuracy. A deep-learning-based super-resolution method is used to artificially increase the pixel density in the same regions. Additionally, the effect of using a single and a stereo camera setup on the accuracy is shown.
Keywords: Automation; Superresolution; Pose estimation; Cameras; Control system; Fiducial markers; computational efficiency; ArUco; 6DoF pose estimation; subpixel; deep learning; visual servoing; simulation

Correlation Analysis of Factors Influencing the Motion Planning Accuracy of Articulated Robots - Kedilioglu, Oguz; Nikol, Markus; Walter, Jonas; Franke, Jörg (2023 9th International Conference on Automation, Robotics and Applications (ICARA), 2023)
The motion planning accuracy of articulated robots can be increased by augmenting them with an objective function. Parameters that influence the absolute accuracy of 6-axis articulated robots can be integrated into such objective functions. However, it is still unclear how to prioritize the various influencing factors so that they can be utilized together instead of separately. Here, it is shown how to rate these factors by analyzing and comparing their impact on the accuracy of the robot. The factors manipulability, smoothness, gear backlash caused by direction change of axis rotation, joint space distance and robot layout are studied in this regard. The evaluation with a 6DoF laser tracker reveals that manipulability and smoothness have the biggest impact. With these results it is possible to combine multiple factors into a comprehensive function and achieve a higher accuracy without the necessity of applying any hardware upgrades.<br

Effiziente KI-Adaption durch synthetische Daten/Efficient AI Adaption using Synthetic Data - Blank, Andreas; Baier, Lukas; Kedilioglu, Oguz; Zhu, Xuebei; Metzner, Maximilian; Franke, Jörg (wt Werkstattstechnik - Online, 2021)
Production is characterized by an antagonism between flexibility and productivity. Deep Learning-based autonomous robot skills for object manipulation offer potential to solve existing challenges. Currently, the effort to generate appropriate datasets to adapt new components is time-consuming. In this research context, we present and evaluate a method for time-efficient data generation for object recognition based on synthetic data. Die Produktion ist geprägt durch einen Antagonismus aus Flexibilität und Produktivität. Objektmanipulation gestützt durch Deep-Learning-basierte, autonome Roboterfähigkeiten bietet Potenzial, bestehende Herausforderungen zu lösen. Der Aufwand zur Erzeugung zweckmäßiger Daten ist allerdings hoch. Im Beitrag vorgestellt und bewertet wird eine Methode zur zeiteffizienten Datengenerierung für die Objekterkennung mittels synthetischer Daten.<br
Keywords: Object Recognition; Machine Learning; Synthetic Data; AI Adaption; Annotation

High-Precision Visual Servoing for the Neutron Diffractometer STRESS-SPEC at MLZ - Landesberger , Martin; Kedilioglu, Oguz; Wang , Lijiu; Gan , Weimin; Kornmeier , Joana Rebelo; Reitelshöfer, Sebastian; Franke, Jörg; Hofmann , Michael (Sensors, 2024)
With neutron diffraction, the local stress and texture of metallic components can be analyzed non-destructively. For both, highly accurate positioning of the sample is essential, requiring the measurement at the same sample location from different directions. Current sample-positioning systems in neutron diffraction instruments combine XYZ tables and Eulerian cradles to enable the accurate six-degree-of-freedom (6DoF) handling of samples. However, these systems are not flexible enough. The choice of the rotation center and their range of motion are limited. Industrial six-axis robots have the necessary flexibility, but they lack the required absolute accuracy. This paper proposes a visual servoing system consisting of an industrial six-axis robot enhanced with a high-precision multi-camera tracking system. Its goal is to achieve an absolute positioning accuracy of better than (Formula presented.) m. A digital twin integrates various data sources from the instrument and the sample in order to enable a fully automatic measurement procedure. This system is also highly relevant for other kinds of processes that require the accurate and flexible handling of objects and tools, e.g., robotic surgery or industrial printing on 3D surfaces.
CRIS-Team Scopus Importer:2024-05-24
Keywords: automation; computer vision; high accuracy; neutron diffraction; residual stress analysis; robotics; texture analysis; visual servoing

PrIcosa: High-Precision 3D Camera Calibration with Non-Overlapping Field of Views - Kedilioglu, Oguz; Nova, Tasnim; Landesberger, Martin; Wang , Lijiu; Hofmann, Michael; Franke, Jörg; Reitelshöfer, Sebastian (Proceedings of the 20th International Joint Conference on Computer Vision, Imaging and Computer Graphics Theory and Applications - Volume 2 VISAPP: VISAPP, 2025)
Multi-camera systems are being used more and more frequently, from autonomous mobile robots to intelligent visual servoing cells. Determining the pose of the cameras to each other very accurately is essential for many applications. However, choosing the most suitable calibration object geometry and utilizing it as effectively as possible still remains challenging. Disadvantageous geometries provide only subpar datasets, increasing the need for a larger dataset and decreasing the accuracy of the calibration results. Moreover, an unrefined calibration method can lead to worse accuracies even with a good dataset. Here, we introduce a probabilistic method to increase the accuracy of 3D camera calibration. Furthermore, we analyze the effects of the calibration object geometry on the data properties and the resulting calibration accuracy for the geometries cube and icosahedron. The source code for this project is available at GitHub (Nova, 2024
Keywords: 3D Camera Calibration; Non-Overlapping Field of Views; Icosahedron; Probabilistic

RGB-D-based Human Detection and Segmentation for Mobile Robot Navigation in Industrial Environments - Kedilioglu, Oguz; Lieret, Markus; Schottenhamml, Julia; Würfl, Tobias; Blank, Andreas; Maier, Andreas; Franke, Jörg (16th International Joint Conference on Computer Vision, Imaging and Computer Graphics Theory and Applications (VISIGRAPP 2021), 2021)

Roboter werden biomechatronische Assistenten - Reitelshöfer, Sebastian; Merz, Nina; Blank, Andreas; Kedilioglu, Oguz; Martin, Sina; Seßner, Julian; Franke, Jörg (2021)
Keywords: Biomechatronik; Human-Centered Robotics